International handbook of workplace trauma support - Hughes, Rick, 1967-; Kinder, Andrew; Cooper, Cary L. (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2012)
"The International Handbook of Workplace Trauma Support provides a comprehensive overview of contemporary standards and best practice techniques for organizations that draws from the latest research findings and experience of clinicians, academics, practitioners, and other leading authorities on trauma support from around the world"--
Front Matter -- The Evolution and Development of Workplace Trauma Support. The Evolution of Models of Early Intervention for Adults: From Inspired Help Giving toward Evidence-based Pragmatism / Roderick J Ørner -- Evidence-based Trauma Management for Organizations: Developments and Prospects / Jo Rick, Rob Briner -- Large-scale Trauma: Institutionalizing Pre- and Post-trauma Prevention, Intervention, and Treatment / Joyce A Adkins, Bryan M Davidson -- Commonalities and New Directions in Post-trauma Support Interventions: From Pathology to the Promotion of Post-traumatic Growth / Stephen Regel, Atle Dyregrov -- The Legal and Business Imperatives to Manage Trauma Effectively. The Trauma Impact on Organizations: Causes, Consequences, and Remedies / Ronald J Burke -- ASSIST: A Model for Supporting Staff in Secure Healthcare Settings after Traumatic Events That Is Expanding into Other European Territories / Annette Greenwood, Carol Rooney, Vittoria Ardino -- SAV-T First: Managing Workplace Violence / Kate Calnan, E K Kelloway, Kathryne E Dupr -- The Occupational Implication of the Prolonged Effects of Repeated Exposure to Traumatic Stress / Alexander C McFarlane -- The Challenge for Effective Interventions in a Violent Society: Boundaries and Crossovers between Workplace and Community / Merle Friedman, Gerrit van Wyk -- Adversity: Reconceptualizing the Post-trauma Response / Kevin Friery -- New Understandings on Models of Trauma Support. The Role and Nature of Early Intervention: The Edinburgh Psychological First Aid and Early Intervention Programs / Chris Freeman, Patricia Graham -- An Organizational Approach to the Management of Potential Traumatic Events: Trauma Risk Management (TRiM) the Development of a Peer Support Process from the Royal Navy to the Police and Emergency Services / Neil Greenberg, Marilyn Wignall -- Evidence-Based Support for Work-related Trauma: The Royal Mail Group Experience / Jo Rick, Andrew Kinder, Steven Boorman -- The Development of a Practice Research Network and Its Use in the Evaluation of the Rewind Treatment of Psychological Trauma in Different Settings / William Andrews, Scott Miller -- The Emergency Behaviour Officer (EBO): The Use of Accurate Behavioral Information in Emergency Preparedness and Response in Public and Private Sector Settings / Mooli Lahad, Ruvie Rogel, Steven Crimando -- Trauma-related Dissociation in the Workplace / Onno van der Hart, Xiao Lu Wang, Roger M Solomon -- The Theory and Practice of Post-trauma Support. Utilization of EMDR in the Treatment of Workplace Trauma / Roger Solomon, Isabel Fernandez -- Trauma Inoculation: Mindful Preparation for the Unexpected / Gordon Turnbull, Rebekah Lwin, Stuart McNab -- How Employee Assistance Programs (EAPs) Respond to Trauma Support and Critical Incident Management: An International Focus / Mandy Rutter -- Training Resilience for High-risk Environments: Towards a Strength-based Approach within the Military / Sylvie Boermans, Roos Delahaij, Hans Korteling, Martin Euwema -- The Organizational Response to Trauma Support. Preparing for and Managing Trauma within Organizations: How to Rehabilitate Employees Back to Work / Andrew Kinder, Jo Rick -- Healing the Traumatized Organization: An Exploration of Post-trauma Recovery and Growth in the Workplace Setting Using the Metaphor of the Nervous System as a Template to Highlight Collective Learning / Tony Buckley, Alison Dunn -- The Management of Emotionally Disturbing Interventions in Fire and Rescue Services: Psychological Triage as a Framework for Acute Support / Erik L J L De Soir -- Working with Tsunami Survivors in South India: The Problem Lies in a Four-Letter Word / Sue Santi Ireson, Hash Patel -- Turning Training into Reality: Considerations When Training Teams for Deployment to Disasters / Gail Rowntree, Mark Akerlund -- Combating the Effects of Post-traumatic Stress and Other Trauma Associated with the Theatre of War / Walter Busuttil -- Trauma Counseling and Psychological Support in the People's Republic of China (PRC) / Xiaoping Zhu, Zhen Wang, Tony Buon -- How Professionals can Help the Traumatized Organization / Pauline Rennie Peyton -- Military Veterans' Mental Health: Long-term Post-trauma Support Needs / Walter Busuttil -- Post-trauma Support: Learning from the Past to Help Shape a Better Future / Rick Hughes, Andrew Kinder, Cary Cooper -- Index.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Post-traumatic stress disorder -- Handbooks, manuals, etc; Psychic trauma -- Handbooks, manuals, etc; Industrial hygiene -- Handbooks, manuals, etc; Mental Health Services; Occupational Health Services; Stress Disorders, Traumatic -- therapy; PSYCHOLOGY -- Industrial & Organizational Psychology; Industrial hygiene; Post-traumatic stress disorder; Psychic trauma; Electronic books; Handbooks and manuals; Electronic books